ENHANCING TEAMGYM PERFORMANCE WITH POWER TRAINING - Kolbjørn Lindberg; Hanne Sødal; Marie Salterød Sjåvik; Thomas Bjørnsen; Fredrik T Vårvik (University of Ljubljana Press (Založba Univerze v Ljubljani), 2024)
Previous studies have highlighted a strong relationship between mechanical lower limb muscle function and TeamGym performance, specifically in terms of difficulty scores in trampette and tumbling disciplines. To date, no intervention study has explored whether enhancing lower limb muscle function can translate to improved TeamGym performance. We recruited eleven national-level TeamGym athletes (four males, seven females) for a quasi-experimental intervention spanning six weeks. The regimen comprised strength training sessions thrice weekly, emphasizing power and maximum strength. Pre- and post-intervention assessments included countermovement jumps, drop jumps, leg press power, 20m sprints, jump and reach, as well as video analyses of trampoline and tumbling performances. In line with prior research, our study uncovers significant correlations between physical test outcomes and TeamGym performance. Notably, leg press power exhibited a robust association with trampoline performance (r=0.95, p<0.001), while drop jump results correlated strongly with tumbling performance (r=0.72, p<0.05). Post-training, only the intervention group displayed a statistically likely uptick in leg press power. Additionally, the intervention group saw an average increase of 0.15±0.2 points in difficulty, contrasting with the control group's negligible change (0.0±0.2).Given the limited sample size in this preliminary pilot study, the results warrant cautious interpretation. Nonetheless, they resonate with prior findings, suggesting that augmenting an athlete's mechanical lower limb muscle function through targeted strength and power training can beneficially influence national-level TeamGym performance.